Geospatial Assessment of Akure Forest Reserve in Ondo State, Nigeria (2022)
Land Use Land Cover (LULC) changes is one of the significant factors that determines the interaction between humans and its environment in the tropics. In Nigeria, the effect of these anthropogenic activities has led to deforestation and consequent degradation. However, there is dearth of information on the dynamics of many forests cover in Southwestern Nigeria, especially in Akure Forest Reserve. Therefore, this study aimed at assessing the LULC change of Akure forest reserve. Landsat imageries (5 TM of 1984, 7 ETM+ of 2000, and 8 OLI/TIRs of 2016 and 2021were obtained and processed. The processed imageries were analyzed using supervised Maximum Likelihood Classification algorithm to determine LULC classes of Akure forest reserve. The LULC classification followed Anderson darling categorization. Five LULC classes were used: Dense Forest (DF), Less Dense Forest (LDF), Built‐Up (BU), Bare Land (BL) and Water Bodies. Normalized difference Vegetation Index (NDVI) was used to determine the greenness of the reserve. Dense Forest has drastically reduced from 82.6% observed in 1984 to 26.41% in 2021, indicating high level of forest deforestation and degradation, while an upsurge was observed in LDF from 1984 (14.19%) to (55.03%) in year 2021. Changes in BU fluctuated between 0.51% in 1984 and 3.16% in 2021. The highest (0.4) and lowest (0.3) NDVI were recorded in 2016 and 2000. Dense forest cover in Akure Forest Reserve has been converted to agricultural activities. Therefore, there is need for conservation of the forest resources to preclude depletion.